(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is an increasing adoption of blockchain technology over different environment for leveraging security features. After reviewing existing blockchain-based approaches, it is noticed that there is still a large scope of improvement towards data security using blockchain. Therefore, this paper considers a case study of healthcare facilities, where the sensitive information of patient are required to be accessed as well as stored using a novel blockchain-based approach. The proposed system contributes towards developing a novel access control policy as well as a cost-effective authentication policy using a simplified hashing scheme. The prime contribution of the study is to prove that without using sophisticated encryption, it is feasible to integrate blockchain with hashing method for offering higher degree of threat mitigation measures by proposed system.